Exploring the risk stratification of carotid plaque hemodynamic using four-dimensional blood flow technology - Zhang, Si-yuan; Zhao, Hong-liang; Song, Xiao-wei; Wu, Jian; Li, Rui (Frontiers in Molecular Biosciences, 2026)
IntroductionCarotid plaque rupture is a major cause of cerebrovascular events. This study explores the integration of hemodynamic parameters with structural biomarkers for improved risk stratification.MethodsFifty-seven patients with moderate-to-severe carotid stenosis underwent 4D-flow magnetic resonance imaging (MRI) and high-resolution MRI. Hemodynamic parameters [wall shear stress (WSS) and velocity] were analyzed using GT-Flow software at upstream, throat, and downstream plaque regions. After comparison of characteristic values between symptomatic and asymptomatic plaques, variables with p < 0.1 were included in the multivariate logistic regression model to identify independent risk factors.ResultsWSS was significantly higher at plaque throat (0.891 ± 0.422 Pa) and downstream (0.971 ± 0.587 Pa) versus upstream (0.649 ± 0.297 Pa; p < 0.001). Symptomatic plaques showed elevated 3D-WSSmean (1.041 ± 0.418 vs. 0.797 ± 0.402 Pa, p = 0.032), WSS up_max (1.345 ± 0.570 vs. 0.970 ± 0.383 Pa, p = 0.004), and stenosis velocity (31.7 ± 9.9 vs. 25.8 ± 10.3 cm/s, p = 0.036). The thin fibrous cap (TFC, OR = 5.34, p = 0.007) and normalized wall index (NWI, adjusted OR = 59.89, p = 0.029) independently predicted symptomatic plaques. The combined model (NWI + TFC + WSS down_max) predicted cerebral ischemic events within 6 months with an AUC of 0.809 (95% CI: 0.699–0.919).ConclusionIntegration of downstream hemodynamic profiling (WSS) with structural biomarkers (TFC and NWI) provides a robust stratification tool for cerebrovascular risk assessment. These quantitative parameters offer potential as molecular diagnostics for plaque vulnerability.